(untitled) (Reflection and Critique Law Magazine, 2020)
This research aims to identify the impacts of decisionism thought on the interpretation of article.48 of the Weimar Constitution from the analysis of the main theoretical assumptions for understanding the concept of sovereign defended by Carl Schmitt. The first part of this paper aimed at establishing a panorama of his decisionist perspective, from his writtings Political Theology and Dictatorship. The second part of the research aimed to understand the decisinism present in the concept of Constitution and guardian of the Constitution in his writtings Constitutional Theory and The Guardian of the Constitution. Finally, the last part was directed to the study of article 48 of the Weimar Constitution from the previously writtings. Therefore, this research has concluded that the analysis of concepts like dictatorship, sovereign, sovereignty and constitution in Carl Schmitt are essential for understanding the interpretation taken from article 48 of the Weimar Constitution by the German jurist, and the consequent definition of who should be the guardian of the Constitution.